2010
DOI: 10.1016/j.jembe.2010.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic and immediate improvements in insular nesting success for threatened sea turtles and shorebirds following predator management

Abstract: Predation critically threatens reproductive success of sea turtles and shorebirds at many of Florida's beaches. We examined the biological and bioeconomic results of predator management on two adjacent barrier islands, Cayo Costa and North Captiva, along Florida's west coast. Both islands suffered severe nesting losses due to predation and disturbance due to raccoons, while Cayo Costa also was impacted by a large population of feral swine. In 2006, our initial year of study, neither island received predator ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 20 publications
(30 reference statements)
0
28
0
Order By: Relevance
“…Other studies have also identified foxes and crows as predators of Piping Plovers (Johnson and Oring 2002;Murphy et al 2003), although this is the first time predation events have been captured by video in Canada. Along the US Eastern seaboard, raccoons are considered a major predator of plover nests (Engeman et al 2010). In our study, only a single raccoon was recorded and it was in Kouchibouguac National Park.…”
Section: Discussionmentioning
confidence: 58%
“…Other studies have also identified foxes and crows as predators of Piping Plovers (Johnson and Oring 2002;Murphy et al 2003), although this is the first time predation events have been captured by video in Canada. Along the US Eastern seaboard, raccoons are considered a major predator of plover nests (Engeman et al 2010). In our study, only a single raccoon was recorded and it was in Kouchibouguac National Park.…”
Section: Discussionmentioning
confidence: 58%
“…Raccoons have exhibited especially rapid increases in population density in urban environments (Smith and Engeman 2002, Prange et al 2003, Hadidian et al 2010, Graser et al 2012) and can cause nearly 100% mortality of turtle nests (e.g., Engeman et al 2005), including Blanding's turtles (Congdon et al 1983Butler and Graham 1995;Standing et al 1999;Kuhns 2010). Furthermore, raccoon management can result in dramatic and immediate improvements in turtle nesting success (Christiansen and Gallaway 1984;Engeman et al 2005Engeman et al , 2010. Raccoon removal prior to the Blanding's turtle nesting season has been carried out annually since 2013 at LC+, has been effective in reducing raccoon density, and appears to have resulted in increased nest success (Urbanek et al 2016).…”
Section: Recruitment Of Head-starts Into Breeding Populationsmentioning
confidence: 99%
“…Critics of this strategy point to turtle life-history analyses that demonstrate that adult survival is the major contributor to population viability for long-lived late-maturing species, and headstarting may do little to reduce extinction risk (Heppell et al 1996;Heppell 1998;Paez et al 2015a, b). Proponents identify unnaturally low juvenile recruitment as a driver of population declines (Congdon et al 1983;Butler and Graham 1995;Standing et al 1999;Engeman et al 2005Engeman et al , 2010, even when adult survival is high, and see headstarting as a possible solution (Vander Haegen et al 2009, Spencer et al 2017. Whether justified or not, head-starting has been implemented for a number of marine, freshwater, and terrestrial turtles.…”
mentioning
confidence: 99%
“…4 See Hannesson (1983), Ragozin and Brown (1985), and Brown et al (2005) for bioeconomic applications making this assumption. 5 It is well documented that foxes, raccoons and other small mammalian predators have higher densities in human land-use areas (Riley et al 1998), reducing bird and amphibian populations (Engeman et al 2010). Other examples include black bears benefiting from roadside forage (Rogers and Allen 1987), birds of prey exploiting schools of salmon near hydroelectric dams (Engeman et al 2009), parasitic cowbirds thriving in residential areas (Borgmann and Morrison 2010) and coyotes adapting to human-disturbed environments (Markovchick-Nicholls et al 2008). prey are only referenced indirectly via the carrying capacity variables.…”
Section: Ecological Modelmentioning
confidence: 99%